2022
DOI: 10.1007/s00402-022-04741-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological comparison between partial and complete resection of the anterior cruciate ligament in patients with mucoid degeneration of the anterior cruciate ligament: a controlled clinical trial

Abstract: Introduction The pathology of a mucoid degeneration of the anterior cruciate ligament (MDACL) has been mentioned in several publications but due to its rare incidence it is not a well-known pathology. Partial or complete resection of the ACL is the option of choice after failed non-surgical treatment. However, the success rate of both surgical techniques and the subsequent risk of an ACL instability is not known. The purpose of this study was to compare the clinical and radiological outcome betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Three studies defined partial debridement as shaving < 50% thickness of the ACL, but seven studies did not have a specific definition for partial debridement [5, 20, 22]. Five studies used only a motorized shaver to perform partial debridement [5, 13, 20, 26, 27]. One of these studies compared a motorized shaver less than 25%, and from 25 to 50% [20].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies defined partial debridement as shaving < 50% thickness of the ACL, but seven studies did not have a specific definition for partial debridement [5, 20, 22]. Five studies used only a motorized shaver to perform partial debridement [5, 13, 20, 26, 27]. One of these studies compared a motorized shaver less than 25%, and from 25 to 50% [20].…”
Section: Resultsmentioning
confidence: 99%
“…The mean postoperative Knee Outcome and Osteoarthritis Score (KOOS) was 78.0 and was reported in only one study [22]. Mean flexion range of motion ranged from 96.4° to 119.0° preoperatively in two studies [26, 28]. Three studies reported mean postoperative ranges of motion ranging from 117.9° to 137.7° [20, 26, 28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetic resonance imaging (MRI) is the gold standard for diagnosing mucoid degeneration of the ACL, and is characterised by a celery stalk sign, with subsequent diagnosis confirmed via tissue biopsy and histology [23]. Management options include non‐surgical measures such as oral analgesics and physiotherapy, whilst operative measures include partial resection of the area affected by degeneration, ACL reconstruction or total resection of the ACL [24, 26].…”
Section: Introductionmentioning
confidence: 99%